COPPER PARTITIONING IN A MELT-VAPOR-BRINE-MAGNETITE-PYRRHOTITE ASSEMBLAGE - Simon A.C.; Pettke T.; Candela P.A.; Piccoli P.M.; Heinrich C.A. (My University, 2006)
The effect of sulfur on the partitioning of Cu in a melt-vapor-brine ? magnetite ? pyrrhotite assemblage has been quantified at 800 °C, 140 MPa, fO2 = nickel-nickel oxide (NNO), log fS2 = - 3.0 (i.e., on the magnetite-pyrrhotite curve at NNO), log fH2 S = - 1.3 and log fSO2 = - 1. All experiments were vapor + brine saturated. Vapor and brine fluid inclusions were trapped in silicate glass and self-healed quartz fractures. Vapor and brine are dominated by NaCl, KCl and HCl in the S-free runs and NaCl, KCl and FeCl2 in S-bearing runs. Pyrrhotite served as the source of sulfur in S-bearing experiments. The composition of fluid inclusions, glass and crystals were quantified by laser-ablation inductively coupled plasma mass spectrometry. Major element, chlorine and sulfur concentrations in glass were quantified by using electron probe microanalysis. Calculated Nernst-type partition coefficients (?2?) for Cu between melt-vapor, melt-brine and vapor-brine are DCuv / m = 63 ? 31, DCub / m = 240 ? 80, and DCuv / b = 0.27 ? 0.10, respectively, in the S-free system. The partition coefficients (?2?) for Cu between melt-vapor, melt-brine and vapor-brine are DCuv/ m = 316 ? 22, DCub / m = 443 ? 68, and DCuv / b = 0.69 ? 0.16, respectively, in the S-bearing system. Apparent equilibrium constants (?1?) describing Cu and Na exchange between vapor and melt and brine and melt were also calculated. The values of KCu,Nav / m are 34 ? 21 and 128 ? 29 in the S-free and S-bearing runs, respectively. The values of KCu,Nab/m are 33 ? 22 and60 ? 5 in the S-free and S-bearing runs, respectively. The data presented here indicate that the presence of sulfur increases the mass transfer of Cu into vapor from silicate melt. Further, the nearly threefold increase in DCuv / b suggests that Cu may be transported as both a chloride and sulfide complex in magmatic vapor, in agreement with hypotheses based on data from natural systems. Most significantly, the data demonstrate that the presence of sulfur enhances the partitioning of Cu from melt into magmatic volatile phases. ? 2006.
Keywords: COPPER; FLUID COMPOSITION; FLUID INCLUSION; MASS TRANSFER; PARTITIONING; SULFUR